The Roles of Deubiquitination in Age-related Diseases - XU Linhui, LI Pengfei, WU Miaomiao, KANG Lihua, JI Min, YU Ying, GUAN Huaijin (Zhongguo quanke yixue)
Deubiquitination, mediated by deubiquitinating enzymes (DUBs), represents a crucial class of post-translational protein modifications. Its primary mechanism involves in the interaction of DUBs with ubiquitinated target proteins, whereby the DUBs cleave or remove ubiquitin chains from these targets, subsequently restoring their expression levels and functional activities. This article systematically reviews the latest research progress on deubiquitination in age-related diseases, covering the types of DUBs, their roles in cellular aging, and the regulatory mechanisms in age-related diseases through different pathways. It also summarizes the research progress in the development of small-molecule drugs targeting DUBs and related mechanisms. This review demonstrates that as the body ages, factors such as decreased protein renewal function and oxidative damage lead to the accumulation of ubiquitinated proteins, resulting in cellular dysfunction. DUBs play an important and complex regulatory role in age-related diseases by modulating mechanisms such as protein homeostasis, mitochondrial function, and cell cycle in aging cells.